A major gene for host response to porcine reproductive and respiratory syndrome is not unfavorably associated with overall performance under nonchallenging conditions in commercial pig lines. Issue 7 (1st July 2017) - Dunkelberger, J. R.; Mathur, P. K.; Lopes, M. S.; Knol, E. F.; Dekkers, J. C. M.
ABSTRACT: A QTL for host response to porcine reproductive and respiratory syndrome (PRRS) was identified in a previous study. The SNP WUR10000125 (WUR) is used as a tag SNP for this QTL. The favorable (B) allele at this SNP is in low frequency in commercial populations, possibly because this allele is unfavorably associated with an important trait under nonchallenging conditions and, therefore, may have been selected against. Therefore, objectives of this study were to estimate the effect of WUR on traits under selection in commercial lines under nonchallenging conditions and to estimate the effect of WUR genotype of parents on performance of crossbred progeny in a commercial-like environment. Data were collected on 4 purebred lines: a Landrace dam line (D1), a Large White dam line (D2), a synthetic sire line (S1), and a Pietrain sire line (S2). Traits analyzed included total number born, number stillborn, farrowing survival, lactation survival, litter mortality, daily feed intake (DFI), backfat, average test daily gain (TGR), average lifetime daily gain (LGR), and Topigs Norsvin selection index (TSI) value, indicative of overall economic value. Deregressed EBV were calculated for each trait (except TSI) and analyzed within line. In the S1 line, AB and BB pigs had significantly lower TGR ( P = 0.002) and LGR ( P = 0.001) than AA pigs but also lower DFI ( P = 0.004). Conversely, AB and BB pigs had significantly higher DFI ( P < 0.001) and AB pigs had significantly higher TGR ( P = 0.03) than AA pigs in the S2 line. The effect of WUR on TSI was not significant for any line ( P ≥ 0.15). Analyses of phenotypic records collected on crossbred progeny of S1 sires and D1 × D2 F1 females showed no significant effect of parent WUR genotype on DFI, backfat, TGR, or LGR ( P ≥ 0.07). In conclusion, the effect of WUR was nonsignificant for most traits but the magnitude and direction of the effect differed by trait and by line. The favorable allele for host response to PRRS was associated with greater DFI and a tendency for greater TGR in the S2 line, but the opposite direction of effect was detected for the S1 line. Regardless of the effect on individual traits, no significant effect of WUR on TSI was detected for any line. Therefore, selecting for the B allele is expected to result in progeny with increased resistance to PRRS without compromising overall economic value under normal, nonchallenging conditions.